A Space for Collaborative Creativity. How Collective Improvising Shapes ‘a Sense of Belonging’ - Verneert, Filip; Nijs, Luc; De Baets, Thomas (Frontiers in Psychology, 2021)
In this contribution, we draw on findings from a non-formal, community music project to elaborate on the relationship between the concept of eudaimonia, as defined by Seligman, the interactive dimensions of collective free improvisation, and the concept of collaborative creativity. The project revolves around The Ostend Street Orkestra (TOSO), a music ensemble within which homeless adults and individuals with a psychiatric or alcohol/drug related background engage in collective musical improvisation. Between 2017 and 2019 data was collected through open interviews and video recordings of rehearsals and performances. Participant data was analyzed through inductive analysis based on the principles of grounded theory. One interesting finding was the discrepancy in the participant interviews between social relationships indicative of a negative affect about social group interaction versus strong feelings of group coherence and belonging. Video recordings of performances and rehearsals showed clear enjoyment and pleasure while playing music. Alongside verbal reflection through one-on-one interviews video recordings and analysis of moment-to moment observations should be used, in order to capture the complexity of community music projects with homeless people. The initial open coding was aligned with the five elements of the PERMA model. Overall, we observed more focus on Relationship (sense of belonging), Engagement (flow in rehearsals and performances) and Meaning (belonging to something greater than yourself) and less on Positive Emotion and Accomplishment (goal setting).